Pertumbuhan dan hasil kubis (Brassica oleracae L.) dalam sistem tumpangsari dengan bawang daun (Allium fistulosum) - , MILA LARAS SETYOWATI ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Cabbage farmers in the highlands often experienced to harvest failure due to environmental factors that do not support the growth and yield of cabbage, one of the factors is the disease. At this time, the main disease that causes farmers failure to harvest cabbage is a disease caused by Plasmodiophora brassicae. Therefore, it is necessary to study the intercropping among cabbage and other crops so that farmers can still harvest the cabbage. The objective of study was to determine the growth and yield of cabbage that grown in the intercropping with scallion. The experiment was conducted at the highland area that located in Daru, Pagergunung Village, Ngablak District, Magelang Regency, Central Java Province in August to November 2011. The research was conducted in randomized complete block design (RCBD) single factor, with 3 blocks as replication. The treatments tested were intercropped cabbage and scallion, and monoculture of cabbage and scallion. The observations were done on several variables of environment, growth and yield of cabbage and scallion. The data were analyzed with t-test. The results showed that intercropping between cabbages with scallion was more profitable when compared to the yield of monoculture of the two species, as intercropping land equivalent ratio (LER) of 2.68. On the same stretch of land can be harvested two commodities, namely cabbage and scallion.